A Historical Analysis of Daqing’s Planning Policies, 1960s-1980s - Zhu, Penglin (A+BE | Architecture and the Built Environment, 2024)
The thesis explores the planning heritage created by the Chinese government’s industrial efforts in Daqing from the late 1950s to the late 1980s. It focuses on how petroleum infrastructure and residential developments reshaped the local environment. By examining Daqing’s planning history through the concept of “planning heritage”, as discussed by both international and Chinese scholars, this research argues that documenting planning practices—particularly by addressing planning failures—provides Chinese historians a path to preserve a planning heritage that may diverge from state-endorsed narratives. Contrasting with the official, heroic portrayal of Daqing’s oilfield development, this work exposes the overlooked and suppressed aspects of mining area planning, construction, and local living conditions. Utilizing the Global Palimpsestic Petroleumscape (GPP) framework, designed initially for capitalist petroleum industries, the study assesses Daqing’s planning policy, rule, and directive path dependencies and the disruptions from political power shifts. By adapting the GPP framework to Daqing’s unique context, this research highlights how these dependencies and interruptions have shaped Daqing’s planning legacy within a state-led socialist system. The thesis challenges dominant narratives and underscores the importance of a balanced historical perspective encompassing both achievements and failures. It aims to serve as a critical resource for scholars in architectural and urban history and planning studies, especially those exploring heritage within complex political frameworks.